Development of Mobile Exam Application to Prevent Student Exam Cheating on High School Computational Thinking Informatics Materials - Mukhamad Khasan Tiarani; Triana Rejekiningsih; Sri Sumaryati (Jurnal Teknologi Pendidikan)
This study aims to develop a mobile-exam application to prevent cheating during online  exams in high school computational thinking. The research follows the 4D development model (Define, Design, Develop, Disseminate) and collects data through questionnaires, observations, pre-test and post-test in control and experimental classes. Sample included 72 respondents divided into control and experimental classes. The analysis involves descriptive and statistical methods to compare test result and cheating frequencies. Result indicate that the use of the mobile exam app significantly decreases cheating occurrences compared to traditional methods. The number of cheating incidents decreased from 20 in the control classes to 5 in the experimental classes, demonstrating the application's effectiveness in promoting academic integrity. Furthermore, the experimental class using the app shows improvement in post-test by 13 points compared to a 5-point increase in the control classes, demonstrating that the app not only prevents cheating but also enhances student learning outcomes. This app contributes to promoting academic integrity in online education settings, offering an innovative solution for improving exam security and student performance.